ANALISIS USAHA TANI PADI SAWAH (Oryza Sativa L) DENGAN ASAP CAIR DAN PEMBENAH TANAH DI DESA PEGALONGAN KECAMATAN PATIKRAJA KABUPATEN BANYUMAS - Victor Bintang Panunggul; Afif Hendri Putranto; Ayu Sitanini; Suwali Suwali (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
This study aims to: 1) determine the value of profits or income in rice farming by providing wood vinegar and soil reformers. 2) determine the cost of production in rice farming by applying wood vinegar and soil reformers. 3) determine the value of the B/C ratio in rice farming by applying wood vinegar and soil reformers.  Analysis of the data used in this study, as follows: 1) Analysis of Break Event Point (BEP) production volume. 2) BEP analysis of production price, and 3) BEP analysis of B/C ratio. The result of the value of income earned by the rice plant farming business is Rp. 7,243,625.00. The value of production costs in rice farming is Rp.15,198,375.00/ha. Analysis of the B / C ratio in rice crop farming obtained a B / C ratio value of 1.43. Then it can be implied that the rice crop farming business at the research site is profitable.